APA: The Easy Way! - Houghton, Peggy M. (Baker College, 2009)
This handbook covers many detailed specifications of the APA style...including in-text citations, source citations, and a sample paper. It also sheds new light on the manual using step-by-step processes and exemplification that enable readers to fulfill APA rules and regulations more...